(untitled) (Research, Society and Development, 2022)
Objective: to analyze the perception of people with quadriplegia due to spinal cord injury about the influence of the use of assistive technology (AT) resources to access computers in their daily lives. Method: Qualitative approach, the Grounded Theory. Twenty-seven semistructured interviews were performed with individuals with quadriplegia assisted in the SARAH of Rehabilitation Hospitals of Brasília. The data were analyzed with ATLAS.ti software. Results: AT for access to computers makes it possible to reduce vulnerability and expand the autonomy of people with severe spinal cord injury, in different perspectives, as well as their social and work reintegration. Conclusion: that it is necessary to include in the care services people with severe spinal cord injury, the possibility of using AT, from the beginning of treatment, with proper monitoring of qualified professionals to guide their use. Therefore, these people’s right of access to AT should be recognized in order to improve their quality of life and achieve human dignity. It becomes an ethical imperative to guarantee these people’s access to AT resources, through the expansion of intersectorial public policies, which cannot be separated from other efforts undertaken by the government to improve the social life of these citizens.